RanGAP1*SUMO1 is phosphorylated at the onset of mitosis and remains associated with RanBP2 upon NPC disassembly - Swaminathan, Sowmya; Kiendl, Florian; Körner, Roman; Lupetti, Raffaella; Hengst, Ludger; Melchior, Frauke (The journal of cell biology, 2004)
The RanGTPase activating protein RanGAP1 has essential functions in both nucleocytoplasmic transport and mitosis. In interphase, a significant fraction of vertebrate SUMO1-modified RanGAP1 forms a stable complex with the nucleoporin RanBP2/Nup358 at nuclear pore complexes. RanBP2 not only acts in the RanGTPase cycle but also is a SUMO1 E3 ligase. Here, we show that RanGAP1 is phosphorylated on residues T409, S428, and S442. Phosphorylation occurs before nuclear envelope breakdown and is maintained throughout mitosis. Nocodazole arrest leads to quantitative phosphorylation. The M-phase kinase cyclin B/Cdk1 phosphorylates RanGAP1 efficiently in vitro, and T409 phosphorylation correlates with nuclear accumulation of cyclin B1 in vivo. We find that phosphorylated RanGAP1 remains associated with RanBP2/Nup358 and the SUMO E2-conjugating enzyme Ubc9 in mitosis, hence mitotic phosphorylation may have functional consequences for the RanGTPase cycle and/or for RanBP2-dependent sumoylation.